THE FINANCIAL PERFORMANCE OF FOOD AND BAVERAGE COMPANIES : ENTERPRISE RISK MANAGEMENT, BUSINESS STRATEGY AND CEO NARCISSISM - Purnomo, Listiya Ike; Ervina Sukmayanti; Ahmad Syifa (Jurnal Studia Akuntansi dan Bisnis (The Indonesian Journal of Management & Accounting), 2024)
The background of this research is the importance of the performance of manufacturing companies to be able to increase the added value of raw materials, require a lot of labor, and the largest foreign exchange earner. Therefore, companies must produce good performance in order to survive in the competition. Company performance is the achievement of company results that refer to predetermined standards within a certain period. This research aims to obtain empirical evidence of the effect of Enterprise Risk Management, Business Strategy, and CEO Narcisism on company financial performance in food and beverage sub-sector companies listed on the IDX in 2018 - 2022. The dependent variable in this study is financial performance, while the independent variables in this study are Enterprise Risk Management, Business Strategy, and CEO Narcsim. This study uses an associative quantitative approach with data sourced from the company's annual report for the period 2018 - 2022. Data analysis with panel data regression with EVIEWS 10 tools. The results of the Enterprise Risk Management variable research with a prob value of 0.6075 indicate that Enterprise Risk Management has no effect on financial performance. The Business Strategy variable with a prob value of 0.0661 means that Business Strategy has no significant effect on financial performance. The CEO Narcisism variable obtained a prob value of 0.0266 indicating that CEO Narcisism has an effect on financial performance.